Implementasi Kegiatan Khitobah untuk Meningkatkan Rasa Percaya Diri dan Tanggung Jawab di MAN 2 Karanganyar - Ahmadi, Fauzan; Rohimah, Siti (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
Education plays an important role in improving the quality of learners, focusing on developing self-confidence and responsibility through khitobah activities. This activity helps students overcome shyness, improve their public speaking skills, and foster an attitude of responsibility towards their duties. At MAN 2 Karanganyar, khitobah is implemented to form a generation that is qualified and able to compete in society with Islamic values. The method used in this research is descriptive qualitative method. The results of this study indicate that through khitobah, students develop public speaking, time management, and organizational skills, as well as learn to take responsibility and express themselves confidently. This activity not only builds communication and leadership skills, but also encourages social awareness, preparing students to apply religious values in daily life and contribute positively to society. The initiative has successfully attracted increased student participation, creating an environment that supports personal growth and skill development.